Criminal Law facing with illness. - Eusebi, Luciano (Medicina e Morale, 2001)
The role of the consent is discussed in comparison to the juridical and criminal qualification of the medical/surgical treatment. It sustains that the principle of self-determination cannot constitute the only indicative criterion to resolve the emergent ethical and juridical issues in biomedicine today, because the danger of a contractualistic and defensive medicine would rise and medicine itself would be conceived not as (human) science, but as mere technical skill. In this sense, different situations in which the consent is impossible or inadequate are underlined. The Author shows that the comparison, to define convergences on the fundamental factors for the guardianship of the human dignity - and therefore to define shared guidelines in particular fields of human activity -, is co-essential to the modern concept of democracy. Particularly, pertinent motivations are developed also in a secular and pluralistic social context with the purpose to maintain the juridical prohibition of the euthanasia both active and passive, in the optics of a solidaristic approach to the suffering. This approach would be compromised from a favourable normative law to the euthanasia. In this sense, an intrinsic limit to the law is determined in the impossibility to legally authorise a physician-patient relationship played upon the death. Of course, the matter of the euthanasia is held separate from the issues regarding the therapeutic obstinacy and the proportionality of a medical intervention. A specific investigation is devoted to the interpretation of the art. 32, the 2nd paragraph, of the Italian Constitution, with respect to the permanent juridical validity of the principle of unavailability of the human life. They are also considered issues concerning the incompetent subjects, the role of the norm under necessity, the assignments of the institutional review boards (also with respect to the responsibility of the members) and the necessity of new juridical models to the prevention of the "adverse" medical events.